The led lighting system powered by photovoltaic (PV) / Abdul Halim Zulkefeli - Zulkefeli, Abdul Halim (2010)
In this era, most of the technology chases to use the renewable energy. Nowadays, fossil fuel which is a major power sources is become fewer from days to days. Besides, the fuel gives a major cause of environmental problems makes the mankind to look for alternative resources in power generation. One of the alternative resources is using solar energy. This project aims mainly to make a save and safe light system which is powered by the photovoltaic. The bulb will be made with the design using LED. LED helps to produced minimum output delivered because LED using a minimum energy. The source comes from the photovoltaic which will convert the solar energy to the electrical energy. This project also aims to design a charger controller to charge a battery. The charging circuit utilizes the three modes of the battery charging process; normal or bulk charge, finishing or float charge and equalizing charge.